Variations in Lipid Profile During Critical Illness - Mehreen Hassan; Tariq Bin Sharif; Aamir Ijaz; Naveed Asif; Azooba Fatima; Afshan Bibi (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine to mean change in levels of Triglycerides (TG), Total cholesterol (TC), High-Density Lipoprotein Cholesterol (HDL-C), and low-density lipoprotein (LDL-C) in critically ill patients at admission,18 hours and 42 hours after admission.